Mametu Nangetu na mata - RIBEIRO FILHO, Pedro Ivan Olaia (Universidade Federal do Pará, 2020)
Traditional communities of African array has a deep relationship with nature and its elements. The forest surrounding the market-place “CEASA” is attended by people from traditional communities. They collect leaves, bark and herbs that the forest gives and offer thanks to the energies and mystics persons of the forest. Mametu Nangetu is a tradition woman that goes to the market-place CEASA sinc she was kid, she has great intimacy with the space. She reaps what nature presents us and also afforests the place. This video is the ethnographic record by during the research process of the project: “Feira Livre; -performa-te cidade: investigação performática, diálogos e outros sabores”. This project was awarded by “Bolsa de Criação, Experimentação, Pesquisa e Divulgação Artística 2015 da Fundação Cultural do Pará”. This record was achieved in one morning we were with the Mansu Nangetu’s community at the CEASA’s fair and forest, and we follow Mametu Nangetu sharing knowledge of our bantu tradition. Katendê is the Lord of Forests and Lord of Jinsaba, the sacred leaves. Mariô is the oil palm leaf and it’s used at the entrances of candomble houses. A CANON G15 machine was used to capture the images.